IMPLEMENTATION OF THE PROBLEM BASED LEARNING MODEL TO IMPROVE CRITICAL THINKING SKILLS OF MADRASAH ALIYAH SANTRI STUDENTS - Mahmudah, Rifa Zakiah; Nugraha, Mulayawan Safwandy (PAI RAFAH, 2024)
Problem Based Learning (PBL) is a learning model that aims to train students' critical thinking and problem-solving skills towards real situations. This research uses qualitative methods with a case study approach that focuses on the implementation of the Problem Based Learning model to improve the critical thinking skills of student students at MA Sunanul Huda Cikaroya, Cisaat, Sukabumi Regency, especially in the subject of Akidah Akhlak. Primary data were obtained through interviews with respondents related to the implementation dimensions, namely planning, organizing, implementing, and evaluating. In the planning stage, teachers introduce PBL and its learning objectives, determine themes and problems, and prepare media and classes. Organizing is done by dividing groups and embedding enthusiasm and motivation to students. Implementation takes place in sequence according to syntax, including pre-learning, learning phases, and post-learning. The evaluation and successful implementation can be seen from the ability of student students to face high-level questions (HOTS), their readiness to handle and solve problems in society, as well as the development of empathetic, analytical, and critical attitudes, as well as resistance to false information (hoaxes).